Analysis Method of Tool Topography Change and Identification of Wear Indicators for Heavy Copper Wire Wedge Bonding - Eichwald, Paul; Sextro, Walter; Althof, Simon; Eacock, Florian; Unger, Andreas; Meyer, Tobias; Guth, Karsten (Proceedings of the 47th International Symposium on Microelectronics)
Wire bonding is the most common technology for connecting electronic components. Due to their efficiency bond interconnections made of copper wire are used for example in the aerospace and medical technology as well as in the fields of renewable energies. One of the main cost factors in the manufacturing process is the consumables like bonding tools. The technological transition to copper as wire material causes significant wear on the millimeter large effective contact area of the bonding tool. This wear leads to a loss by a factor of 30 of the number of reliable interconnections which can be produced by a single tool. To reduce setting-up time in the production and minimizing costs, an enlarged bonding tool lifetime is desirable. Consequently a better understanding of wear and recognition of wear pattern is required. Therefore, the paper presents an analyzing method of the tool topography change of a heavy wire bonding tool by using a confocal microscope. Furthermore, the paper discusses the identification of the main wear indicators by the help of the named topography change for different bond parameters, like ultrasonic power and tool geometry. Reference topography has been carried out by choosing typical parameters of the production line. To judge whether the quality requirement of the bond connections made by a single tool cannot be fulfilled shear test of the source bond have been carried out after a defined number of produced bond connections. Main steps of analysis: (I)Topography of the tool surface is sampled after a defined number of bonds by means of a confocal microscope to detect the wear progress.(II)The recorded data is filtered using Matlab. So, measurement errors can be eliminated and the topography can be overlaid more easy to identify differences between diverse tools or differences in wear stages of the same tool.(III)The subsequent discretization of the topography into sub volumes allows to (IV)describe the loss of volume depending on the position in the groove. Thereby, intermediate status of wear of one tool can be used to obtain a persistent description of the topography change over the number of produced bonds by interpolating the confocal data. Afterwards the persistent change of the groove flank has been analyzed for the named test series to identify the main wear indicators and their effect on shear forces. All worn tools show dominant areas for volume loss especially for plastic deformation and accordingly abrasion. These wear mechanism can be referred to the change of main parts of the groove geometry like the rounding of the front and back radius. The most volume loss was identified in the upper part of the tool flanks or rather at the transition from the groove flank to the front or back radius. Furthermore the observation of the center of the groove flank shows just a little change in volume. All in all, the identification of the wear indicators will be discussed with the objective of increasing the tool lifetime by optimizing the tool geometry without losses in bond quality and reliability.
Keywords: wedge/wedge bonding; copper wire; tool wear

Dependability of Self-Optimizing Mechatronic Systems - Gausemeier, Jürgen; Josef Rammig, Franz; Schäfer, Wilhelm; Sextro, Walter
Intelligent technical systems, which combine mechanical, electrical and software engineering with methods from control engineering and advanced mathematics, go far beyond the state of the art in mechatronics and open up fascinating perspectives. Among these systems are so-called self-optimizing systems, which are able to adapt their behavior autonomously and flexibly to changing operating conditions. The Collaborative Research Center 614 "Self-optimizing concepts and structures in mechanical engineering" pursued the long-term aim to enable others to develop dependable self-optimizing systems. Assuring their dependability poses new challenges. However, self-optimization also offers the possibility to adapt the system's behavior to improve dependability during operation. The aim of this book is to provide methods and techniques to master the challenges and to exploit the possibilities given by self-optimization. The reader will be able to develop self-optimizing systems that fulfill and surpass today’s dependability requirements easily. This book is directed to researchers and practitioners alike. It gives a brief introduction to the holistic development approach for self-optimizing mechatronic systems and the steps required to assure a dependable product design starting with the very early conceptual design phase. A guideline to select suitable methods for each step and the methods themselves are included. Each method is individually introduced, many examples and full references are given.

Reliability analysis of ultrasonic power transducers - Hemsel, Tobias; Bornmann, Peter; Morita, Takeshi; Sondermann-Wölke, Christoph; Sextro, Walter (Archive of Applied Mechanics)
Keywords: Reliability; Ultrasonic power transducers; FMEA

High-velocity operation of piezoelectric inertia motors: experimental validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Archive of Applied Mechanics)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. It has been shown previously in theoretical investigations that higher velocities and smoother movements can be obtained if these steps do not contain phases of stiction (''stick-slip`` operation), but use sliding friction only (''slip-slip`` operation). One very promising driving option for such motors is the superposition of multiple sinusoidal signals or harmonics. In this contribution, the theoretical results are validated experimentally. In this context, a quick and reliable identification process for parameters describing the friction contact is proposed. Additionally, the force generation potential of inertia motors is investigated theoretically and experimentally. The experimental results confirm the theoretical result that for a given maximum frequency, a signal with a high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion, while the maximum motor force is obtained with signals containing more harmonics. These results are of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Inertia motor; High velocity; Stick-slip motor; Slip-slip operation; Friction parameter identification

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

PEM fuel cell prognostics using particle filter with model parameter adaptation - Kimotho, James Kuria; Meyer, Tobias; Sextro, Walter (Prognostics and Health Management (PHM), 2014 IEEE Conference on)
Application of prognostics and health management (PHM) in the field of Proton Exchange Membrane (PEM) fuel cells is emerging as an important tool in increasing the reliability and availability of these systems. Though a lot of work is currently being conducted to develop PHM systems for fuel cells, various challenges have been encountered including the self-healing effect after characterization as well as accelerated degradation due to dynamic loading, all which make RUL predictions a difficult task. In this study, a prognostic approach based on adaptive particle filter algorithm is proposed. The novelty of the proposed method lies in the introduction of a self-healing factor after each characterization and the adaption of the degradation model parameters to fit to the changing degradation trend. An ensemble of five different state models based on weighted mean is then developed. The results show that the method is effective in estimating the remaining useful life of PEM fuel cells, with majority of the predictions falling within 5% error. The method was employed in the IEEE 2014 PHM Data Challenge and led to our team emerging the winner of the RUL category of the challenge.
Keywords: ageing; particle filtering (numerical methods); proton exchange membrane fuel cells; remaining life assessment; PEM fuel cell prognostics; PHM; RUL predictions; accelerated degradation; adaptive particle filter algorithm; dynamic loading; model parameter adaptation; prognostics and health management; proton exchange membrane fuel cells; remaining useful life estimation; self-healing effect; Adaptation models; Data models; Degradation; Estimation; Fuel cells; Mathematical model; Prognostics and health management

An approach for feature extraction and selection from non-trending data for machinery prognosis - Kimotho, James Kuria; Sextro, Walter (Proceedings of the Second European Conference of the Prognostics and Health Management Society 2014)
With the paradigm shift towards prognostic and health management (PHM) of machinery, there is need for reliable PHM methodologies with narrow error bounds to allow maintenance engineers take decisive maintenance actions based on the prognostic results. Prognostics is mainly concerned with the estimation of the remaining useful life (RUL) or time to failure (TTF). The accuracy of PHM methods is usually a function of the features extracted from the raw data obtained from sensors. In cases where the extracted features do not display clear degradation trends, for instance highly loaded bearings, the accuracy of the state of the art PHM methods is significantly affected. The data which lacks clear degradation trend is referred to as non-trending data. This study presents a method for extracting degradation trends from non-trending condition monitoring data for RUL estimation. The raw signals are first filtered using a discrete wavelet transform (DWT) denoising filter to remove noise from the acquired signals. Time domain, frequency domain and time-frequency domain features are then extracted from the filtered signals. An autoregressive model is then applied to the extracted features to identify the degradation trends. Features representing the maximum health information are then selected based on a performance evaluation criteria using extreme learning machine (ELM) algorithm. The selected features can then be used as inputs in a prognostic algorithm. The feasibility of the method is demonstrated using experimental bearing vibration data. The performance of the method is evaluated on the accuracy of RUL estimation and the results show that the method can be used to accurately estimate RUL with a maximum error of 10%.
Keywords: autoregressive model ELM feature extraction feature selection non-trending Remaining useful Life

Optimal Parameter Tuning for Multiclass Support Vector Machines in Machinery Health State Estimation - Kimotho, James Kuria; Sextro, Walter (PAMM)
The increasing demand for high reliability, safety and availability of technical systems calls for innovative maintenance strategies. The use of prognostic health management (PHM) approach where maintenance action is taken based on current and future health state of a component or system is rapidly gaining popularity in the maintenance industry. Multiclass support vector machines (MC-SVM) has been identified as a promising algorithm in PHM applications due to its high classification accuracy. However, it requires parameter tuning for each application, with the objective of minimizing the classification error. This is a single objective optimization problem which requires the use of optimization algorithms that are capable of exhaustively searching for the global optimum parameters. This work proposes the use of hybrid differential evolution (DE) and particle swarm optimization (PSO) in optimally tuning the MC-SVM parameters. DE identifies the search limit of the parameters while PSO finds the global optimum within the search limit. The feasibility of the approach is verified using bearing run-to-failure data and the results show that the proposed method significantly increases health state classification accuracy.

Tire footprint analysis depending on the elastokinematics of a multi-link suspension system using multi-body dynamics simulation - Kohl, Sergej; Sextro, Walter; Zuber, Armin (PAMM)
An automotive suspension system represents one of the most complex and important systems in a passenger vehicle, which has to ensure a robust and optimized contact between the wheels and the road at any time. For improving a suspension system it is important to take an investigative look at the interaction between suspension, tire and road dynamics. Thus a part of a study into aspects of suspension modeling on multi-body simulations of rear multi-link suspension system dynamics with focus on the tire footprint area is presented in this work.

Conclusion and Outlook - Meyer, Tobias; Priesterjahn, Claudia; Sextro, Walter (Dependability of Self-Optimizing Mechatronic Systems)

Closed-loop Control System for the Reliability of Intelligent Mechatronic Systems - Meyer , Tobias; Sextro, Walter (Proceedings of the Second European Conference of the Prognostics and Health Management Society 2014)
So-called reliability adaptive systems are able to adapt their system behavior based on the current reliability of the system. This allows them to react to changed operating conditions or faults within the system that change the degradation behavior. To implement such reliability adaptation, self-optimization can be used. A self-optimizing system pursues objectives, of which the priorities can be changed at runtime, in turn changing the system behavior. When including system reliability as an objective of the system, it becomes possible to change the system based on the current reliability as well. This capability can be used to control the reliability of the system throughout its operation period in order to achieve a pre-defined or user-selectable system lifetime. This way, optimal planning of maintenance intervals is possible while also using the system capabilities to their full extent. Our proposed control system makes it possible to react to changed degradation behavior by selecting objectives of the self-optimizing system and in turn changing the operating parameters in a closed loop. A two-stage controller is designed which is used to select the currently required priorities of the objectives in order to fulfill the desired usable lifetime. Investigations using a model of an automotive clutch system serve to demonstrate the feasibility of our controller. It is shown that the desired lifetime can be achieved reliably.
Keywords: self-optimization reliability adaptive

Method to Identify Dependability Objectives in Multiobjective Optimization Problem - Meyer , Tobias; Sondermann-Wölke, Christoph; Sextro, Walter (Conference Proceedings of the 2nd International Conference on System-Integrated Intelligence)
Intelligent mechatronic systems, such as self-optimizing systems, allow an adaptation of the system behavior at runtime based on the current situation. To do so, they generally select among several pre-defined working points. A common method to determine working points for a mechatronic system is to use model-based multiobjective optimization. It allows finding compromises among conflicting objectives, called objective functions, by adapting parameters. To evaluate the system behavior for different parameter sets, a model of the system behavior is included in the objective functions and is evaluated during each function call. Intelligent mechatronic systems also have the ability to adapt their behavior based on their current reliability, thus increasing their availability, or on changed safety requirements; all of which are summed up by the common term dependability. To allow this adaptation, dependability can be considered in multiobjective optimization by including dependability-related objective functions. However, whereas performance-related objective functions are easily found, formulation of dependability-related objective functions is highly system-specific and not intuitive, making it complex and error-prone. Since each mechatronic system is different, individual failure modes have to be taken into account, which need to be found using common methods such as Failure-Modes and Effects Analysis or Fault Tree Analysis. Using component degradation models, which again are specific to the system at hand, the main loading factors can be determined. By including these in the model of the system behavior, the relation between working point and dependability can be formulated as an objective function. In our work, this approach is presented in more detail. It is exemplified using an actively actuated single plate dry clutch system. Results show that this approach is suitable for formulating dependability-related objective functions and that these can be used to extend system lifetime by adapting system behavior.
Keywords: Self-optimization; multiobjective optimization; objective function; dependability; intelligent system; behavior adaptation

Thermo-Mechanical Model for Wheel Rail Contact using Coupled Point Contact Elements - Neuhaus, Jan; Sextro, Walter (Proceedings of the 5th International Conference on Computational Methods)
A model to calculate the locally resolved tangential contact forces of the wheel rail contact with respect to contact kinematics, material and surface properties as well as temperature is introduced. The elasticity of wheel and rail is modeled as an elastic layer consisting of point contact elements connected by springs to each other and to the wheel. Each element has two degrees of freedom in tangential directions. The resulting total stiffness matrix is reduced to calculate only the position of the elements in contact. Friction forces as well as contact stiffnesses are incorporated by a nonlinear force-displacement characteristic, which originates from a detailed contact model. The contact elements are transported through the contact zone in discrete time steps. After each time step an equilibrium is calculated. For all elements, their temperature and its influence on local friction are regarded by calculating friction power and temperature each time step.
Keywords: Rolling Contact; Discrete Elements; Contact Stiffness; Temperature

Contact Modeling in Multibody Systems with Elastic Bodies in High-Frequency Applications - Schulze, Sebastian; Sextro, Walter; Grüter, Frank (PAMM)
This paper discusses the refinement of multibody models by integration of flexible bodies and by considering nonlinearities from contacts. It presents common approaches for contact modeling in multibody simulations and strategies to include flexible bodies. A contact model is implemented in the elastic multibody model. Experimental results show that significant effects of system dynamics can be modeled by use of a multibody model including elastic bodies and contacts.

Time-efficient dynamic analysis of structures exhibiting nonlinear peak bending - Sprock, Christian; Sextro, Walter (Instrumentation and Measurement Technology Conference (I2MTC) Proceedings, 2014 IEEE International)
A measurement method is presented that combines the advantages of the multisine measurement technique with a prediction method for peak bending behavior. This combination allows the analysis of the dynamic behavior of mechanical structures at distinctly reduced measurement durations and has the advantage of reducing high excitation impacts on the structure under test.
Keywords: bending; dynamic testing; measurement; structural engineering; vibrations; measurement durations; mechanical structures; multisine measurement technique; nonlinear peak bending behavior; prediction method; time-efficient dynamic analysis; Heuristic algorithms; Nonlinear systems; Oscillators; Time measurement; Time-frequency analysis; Vibrations

Time-efficient analysis of nonlinear dynamic behavior. - Sprock, Christian; Sextro, Walter (Proceedings in Applied Mathematics and Mechanics 14 (2014), Nr. 1,)
Many nonlinear mechanical oscillators show excitation-dependent behavior. In this paper, a new measurement approach is presented to analyze such structures. The main advantage of the presented method is the high efﬁciency, since measurement duration and loads to the structure are signiﬁcantly reduced.

Time-efficient analysis of nonlinear peak bending behavior. - Sprock, Christian; Sextro, Walter (Proceedings of ISMA - International Conference of Noise and Vibration. 2014)
A measurement method is presented that combines the advantages of the multisine measurement technique with a prediction method for peak bending behavior. This combination allows the analysis of the dynamic behavior of mechanical structures at distinctly reduced measurement durations and has the advantage of reducing high excitation impacts on the structure under test. After a brief presentation of the algorithm, the validity scope of the approach is investigated with emphasis on an exemplary error investigation.

Vibration Analysis of Mechanical Structures using Multisine Excitation Techniques - Sprock, Christian; Sextro, Walter (Proceedings of 31st Danubia-Adria Symposium. 2014)

Introduction to Self-optimization and Dependability - Trächtler, Ansgar; Hölscher, Christian; Rasche, Christoph; Priesterjahn, Claudia; Zimmer, Detmar; Henning Keßler, Jan; Stahl, Katharin; Flaßkamp, Kathrin; Vaßholz, Mareen; Krüger, Martin; Dellnitz, Michael; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Case Study - Trächtler, Ansgar; Kleinjohann, Bernd; Heinzemann, Christian; Rasche, Christoph; Priesterjahn, Claudia; Steenken, Dominik; Wehrheim, Heike; Gausemeier, Jürgen; Flaßkamp, Kathrin; Kleinjohann, Lisa; Krüger, Martin; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Experimental and Numerical Simulation Study of Pre-Deformed Heavy Copper Wire Wedge Bonds - Unger, Andreas; Sextro, Walter; Althoff, Simon; Eichwald, Paul; Meyer, Tobias; Eacock, Florian; Brökelmann, Michael (Proceedings of the 47th International Symposium on Microelectronics (IMAPS))
Power semiconductor modules are used to control and switch high electrical currents and voltages. Within the power module package wire bonding is used as an interconnection technology. In recent years, aluminum wire has been used preferably, but an ever-growing market of powerful and efficient power modules requires a material with better mechanical and electrical properties. For this reason, a technology change from aluminum to copper is indispensable. However, the copper wire bonding process reacts more sensitive to parameter changes. This makes manufacturing reliable copper bond connections a challenging task. The aim of the BMBF funded project Itsowl-InCuB is the development of self-optimizing techniques to enable the reliable production of copper bond connections under varying conditions. A model of the process is essential to achieve this aim. This model needs to include the dynamic elasto-plastic deformation, the ultrasonic softening effect and the proceeding adhesion between wire and substrate. This paper focusses on the pre-deformation process. In the touchdown phase, the wire is pressed into the V-groove of the tool and a small initial contact area between wire and substrate arise. The local characteristics of the material change abruptly because of the cold forming. Consequently, the pre-deformation has a strong effect on the joining process. In [1], a pre-cleaning effect during the touchdown process of aluminum wires by cracking of oxide layers was presented. These interactions of the process parameters are still largely unknown for copper. In a first step, this paper validates the importance of modeling the pre-deformation by showing its impact on the wire deformation characteristic experimentally. Creating cross-section views of pre-deformed copper wires has shown a low deformation degree compared to aluminum. By using a digital microscope and a scanning confocal microscope an analysis about the contact areas and penetration depths after touchdown has been made. Additionally, it has to be taken into account that the dynamical touchdown force depends on the touchdown speed and the touchdown force set in the bonding machine. In order to measure the overshoot in the force signals, a strain gauge sensor has been used. Subsequently, the affecting factors have been interpreted independently Furthermore, the material properties of copper wire have been investigated with tensile tests and hardness measurements. In a second step, the paper presents finite element models of the touchdown process for source and destination bonds. These models take the measured overshoot in the touchdown forces into account. A multi-linear, isotropic material model has been selected to map the material properties of the copper. A validation of the model with the experimental determined contact areas, normal pressures and penetration depths reveals the high model quality. Thus, the simulation is able to calculate and visualize the three dimensional pre-deformation with an integrated material parameter of the wire if the touchdown parameters of the bonding machine are known. Based on the calculated deformation degrees of wire and substrate, it is probably possible to investigate the effect of the pre-deformation on the pre-cleaning phase in the copper wire bonding.
Keywords: pre-deformation; copper wire bonding; finite element model

Data-driven Modeling of the Ultrasonic Softening Effect for Robust Copper Wire Bonding - Unger, Andreas; Sextro, Walter; Althoff, Simon; Meyer, Tobias; Brökelmann, Michael; Neumann, Klaus; Reimann, René Felix; Guth, Karsten; Bolowski, Daniel (Proceedings of 8th International Conference on Integrated Power Electronic Systems)
In power electronics, ultrasonic wire bonding is used to connect the electrical terminals of power modules. To implement a self-optimization technique for ultrasonic wire bonding machines, a model of the process is essential. This model needs to include the so called ultrasonic softening effect. It is a key effect within the wire bonding process primarily enabling the robust interconnection between the wire and a substrate. However, the physical modeling of the ultrasonic softening effect is notoriously difficult because of its highly non-linear character and the absence of a proper measurement method. In a first step, this paper validates the importance of modeling the ultrasonic softening by showing its impact on the wire deformation characteristic experimentally. In a second step, the paper presents a data-driven model of the ultrasonic softening effect which is constructed from data using machine learning techniques. A typical caveat of data-driven modeling is the need for training data that cover the considered domain of process parameters in order to achieve accurate generalization of the trained model to new process configurations. In practice, however, the space of process parameters can only be sampled sparsely. In this paper, a novel technique is applied which enables the integration of prior knowledge about the process into the datadriven modeling process. It turns out that this approach results in accurate generalization of the data-driven model to unseen process parameters from sparse data.

On the Relation between Innovation and Competion: The Case of Energy Industry - Brummel, NinaMadeleine

On Stabilizing Departures in Overlay Networks - Foreback, Dianne; Koutsopoulos, Andreas; Nesterenko, Mikhail; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 16th International Symposium on Stabilization, Safety, and Security of Distributed Systems)
A fundamental problem for peer-to-peer systems is to maintain connectivity while nodes are leaving, i.e., the nodes requesting to leave the peer-to-peer system are excluded from the overlay network without affecting its connectivity. There are a number of studies for safe node exclusion if the overlay is in a well-defined state initially. Surprisingly, the problem is not formally studied yet for the case in which the overlay network is in an arbitrary initial state, i.e., when looking for a self-stabilizing solution for excluding leaving nodes. We study this problem in two variants: the Finite Departure Problem (FDP) ) and the Finite Sleep Problem (FSP). In the FDP the leaving nodes have to irrevocably decide when it is safe to leave the network, whereas in the FSP, this leaving decision does not have to be final: the nodes may resume computation if necessary. We show that there is no self-stabilizing distributed algorithm for the FDP, even in a synchronous message passing model. To allow a solution, we introduce an oracle called NIDEC and show that it is sufficient even for the asynchronous message passing model by proposing an algorithm that can solve the FDP using NIDEC. We also show that a solution to the FSP does not require an oracle.

General relation for group delay and the relevance of group delay for refractometric sensing - Hoekstra, Hugo J. W. M.; Hammer, Manfred (Journal of the Optical Society of America B)
The relevance of our definition for sensitivity in refractometric sensing, being the relative change in the transmittance of a certain output channel of an optical device over the change in the refractive index of the probed material, is discussed. It is compared to one based on spectral shift per refractive index unit change. Further, there is discussion on how group delay and sensitivity are interrelated and can be converted into each other and which physical quantities are relevant for high sensitivity. As a by-product of the theory presented, a general expression relating group delay and the ratio of the time-averaged optical energy and the input power is presented.
Keywords: tet_topic_waveguide

Normalizing Heterogeneous Service Description Models with Generated QVT Transformations - Schwichtenberg, Simon; Gerth, Christian; Huma, Zille; Engels, Gregor (Proceedings of the 10th European Conference on Modelling Foundations and Applications (ECMFA))
Service Oriented Architectures (SOAs) enable the reuse and substitution of software services to develop highly flexible software systems. To benefit from the growing plethora of available services, sophisticated service discovery approaches are needed that bring service requests and offers together. Such approaches rely on rich service descriptions, which specify also the behavior of provided/requested services, e.g., by pre- and postconditions of operations. As a base for the specification a data schema is used, which specifies the used data types and their relations. However, data schemas are typically heterogeneous wrt. their structure and terminology, since they are created individually in their diverse application contexts. As a consequence the behavioral models that are typed over the heterogeneous data schemas, cannot be compared directly. In this paper, we present an holistic approach to normalize rich service description models to enable behavior-aware service discovery. The approach consists of a matching algorithm that helps to resolve structural and terminological heterogeneity in data schemas by exploiting domain-specific background ontologies. The resulting data schema mappings are represented in terms of Query View Transformation (QVT) relations that even reflect complex n:m correspondences. By executing the transformation, behavioral models are automatically normalized, which is a prerequisite for a behavior-aware operation matching.

Simulation of Planar Photonic Resonators - Declair, Stefan; Förstner, Jens (Handbook of Optical Microcavities)
Keywords: tet_topic_phc

Multilevel Network Games - Abshoff, Sebastian; Cord-Landwehr, Andreas; Jung, Daniel; Skopalik, Alexander (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
We consider a multilevel network game, where nodes can improvetheir communication costs by connecting to a high-speed network.The n nodes are connected by a static network and each node can decideindividually to become a gateway to the high-speed network. The goalof a node v is to minimize its private costs, i.e., the sum (SUM-game) ormaximum (MAX-game) of communication distances from v to all othernodes plus a fixed price α > 0 if it decides to be a gateway. Between gatewaysthe communication distance is 0, and gateways also improve othernodes’ distances by behaving as shortcuts. For the SUM-game, we showthat for α ≤ n − 1, the price of anarchy is Θ (n/√α) and in this rangeequilibria always exist. In range α ∈ (n−1, n(n−1)) the price of anarchyis Θ(√α), and for α ≥ n(n − 1) it is constant. For the MAX-game, weshow that the price of anarchy is either Θ (1 + n/√α), for α ≥ 1, orelse 1. Given a graph with girth of at least 4α, equilibria always exist.Concerning the dynamics, both games are not potential games. For theSUM-game, we even show that it is not weakly acyclic.

Modeling and Matching of Reputation of Services in On-The-Fly Computing - Bano, Dorina

Minimum Linear Arrangement of Series-Parallel Graphs - Scheideler, Christian; Eikel, Martina; Setzer, Alexander (Proceedings of the 12th Workshop on Approximation and Online Algorithms (WAOA))
We present a factor $14D^2$ approximation algorithm for the minimum linear arrangement problem on series-parallel graphs, where $D$ is the maximum degree in the graph. Given a suitable decomposition of the graph, our algorithm runs in time $O(|E|)$ and is very easy to implement. Its divide-and-conquer approach allows for an effective parallelization. Note that a suitable decomposition can also be computed in time $O(|E|\log{|E|})$ (or even $O(\log{|E|}\log^*{|E|})$ on an EREW PRAM using $O(|E|)$ processors). For the proof of the approximation ratio, we use a sophisticated charging method that uses techniques similar to amortized analysis in advanced data structures. On general graphs, the minimum linear arrangement problem is known to be NP-hard. To the best of our knowledge, the minimum linear arrangement problem on series-parallel graphs has not been studied before.

Memory Security in Reconfigurable Computers: Combining Formal Verification with Monitoring - Wiersema, Tobias; Drzevitzky, Stephanie; Platzner, Marco (Proceedings of the International Conference on Field-Programmable Technology (FPT))
Ensuring memory access security is a challenge for reconfigurable systems with multiple cores. Previous work introduced access monitors attached to the memory subsystem to ensure that the cores adhere to pre-defined protocols when accessing memory. In this paper, we combine access monitors with a formal runtime verification technique known as proof-carrying hardware to guarantee memory security. We extend previous work on proof-carrying hardware by covering sequential circuits and demonstrate our approach with a prototype leveraging ReconOS/Zynq with an embedded ZUMA virtual FPGA overlay. Experiments show the feasibility of the approach and the capabilities of the prototype, which constitutes the first realization of proof-carrying hardware on real FPGAs. The area overheads for the virtual FPGA are measured as 2x-10x, depending on the resource type. The delay overhead is substantial with almost 100x, but this is an extremely pessimistic estimate that will be lowered once accurate timing analysis for FPGA overlays become available. Finally, reconfiguration time for the virtual FPGA is about one order of magnitude lower than for the native Zynq fabric.

Measuring Transformation-induced Uncertainty in Service Matching: A Feasibility Study - Bunse, Mirko

Matching of Incomplete Service Specifications Exemplified by Privacy Policy Matching - Platenius, Marie Christin; Arifulina, Svetlana; Petrlic, Ronald; Schäfer, Wilhelm (Proceedings of the 4th International Workshop on Adaptive Services for the Future Internet)
Service matching approaches determine to what extent a provided service matches a requester's requirements. This process is based on service specifications describing functional (e.g., signatures) as well as non-functional properties (e.g., privacy policies). However, we cannot expect service specifications to be complete as providers do not want to share all details of their services' implementation. Moreover, creating complete specifications requires much effort. In this paper, we propose a novel service matching approach taking into account a service's signatures and privacy policies. In particular, our approach applies fuzzy matching techniques that are able to deal with incomplete service specifications. As a benefit, decision-making based on matching results is improved and service matching becomes better applicable in practice.

Market-optimized Service Specification and Matching - Arifulina, Svetlana; Platenius, Marie Christin; Gerth, Christian; Becker, Steffen; Engels, Gregor; Schäfer, Wilhelm (Proceedings of the 12th International Conference on Service Oriented Computing (ICSOC 2014))
Various approaches in service engineering are based on servicemarkets where brokers use service matching in order to performservice discovery. For matching, a broker translates the specifications ofproviders' services and requesters' requirements into her own specificationlanguage, in order to check their compliance using a matcher. Thebroker's success depends on the configuration of her language and itsmatcher because they in uence important properties like the effort forproviders and requesters to create suitable specifications as well as accuracyand runtime of matching. However, neither existing service specification languages, nor existing matching approaches are optimized insuch way. Our approach automatically provides brokers with an optimalconfiguration of a language and its matcher to improve her success ina given market with respect to her strategy. The approach is based onformalized configuration properties and a predefined set of configurationrules.

Machtverteilungen von Koalitionen im Fokus der politischen Realität - Martin Lohre, Tobias

Kooperative Verhandlungen im duopolistischen Wettbewerb - eine spieltheoretische Analyse - van Straaten, Dirk

Koalitionsbildung bei mehrdimensionalen Verhandlungsproblemen - Degraf, Olga

Spatially resolved optical emission of cubic GaN/AlN multi-quantum well structures - As, D.J.; Kemper, R.; Mietze, C.; Wecker, T.; Lindner, Jörg; Veit, P.; Dempewolf, A.; Bertram, F.; Christen, J. (MRS Proceedings)
In this contribution we report on the optical properties of cubic AlN/GaN asymmetric multi quantum wells (MQW) structures on 3C-SiC/Si (001) substrates grown by radio-frequency plasma-assisted molecular beam epitaxy (MBE). Scanning transmission electron microscopy (STEM) and spatially resolved cathodoluminescence (CL) at room temperature and at low temperature are used to characterize the optical properties of the cubic AlN/GaN MQW structures. An increasing CL emission intensity with increasing film thickness due to the improved crystal quality was observed. This correlation can be directly connected to the reduction of the linewidth of x-ray rocking curves with increasing film thickness of the c-GaN films. Defects like stacking faults (SFs) on the {111} planes, which also can be considered as hexagonal inclusions in the cubic crystal matrix, lead to a decrease of the CL emission intensity. With low temperature CL line scans also monolayer fluctuations of the QWs have been detected and the observed transition energies agree well with solutions calculated using a one-dimensional (1D) Schrödinger-Poisson simulator.

A template-assisted self-organization process for the formation of a linear arrangement of pairs of metallic tips - Brassat, Katharina; Lindner, Jörg (MRS Proceedings)
A novel process for the formation of pairs of opposing metallic nanotips within linear trenches on a silicon wafer is investigated in detail. The process is based on a spreading knife technique typically used in nanosphere lithography to generate monolayers of colloidal polystyrene beads. Here it is applied to initiate self-assembly of spheres in long linear trenches acting as a template for the sphere arrangement. The optimum blade velocity to deposit the spheres selectively and densely packed in the trench depends on the trench surface fraction and can be described by a modified Dimitrov model. It is demonstrated that the spheres can be used as a shadow mask to deposit metallic nanotips in a channel, which are electrically interconnected on each side of the trench, possibly enabling the control and manipulation of nanoobjects in the channel.

Template-assisted self-assembly process for the formation of nanogap electrodes - Brassat, Katharina; Wahle, M.; Lindner, Jörg

Tuning the distance between opposing metallic nanotips formed by a template assisted self-assembly process - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Surface Patterning with Nanosphere Lithography - Brassat, Katharina; Brodehl, Christoph; Pauly, Johannes; Drude, Dennis; Achtelik, Jörn; Riedl, Thomas; Lindner, Jörg

Self-assembly for the directed self-assembly of smaller objects in a microfluidic channel - Brassat, Katharina; Brodehl, Christoph; Wahle, M.; Lindner, Jörg

Double-Angle-Resolved Nanosphere Lithography - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Nanosphere lithography for the creation of nanoparticle arrays with tailored shape - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Fabrication of Arrays of Nanoparticles with Arbitrarily Designed Shape - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Investigation of cubic GaN quantum dots grown by the Stranski-Krastanov process - Bürger, M.; Lindner, Jörg; Reuter, Dirk; As, D.J.

Numerical analysis of defects in colloidal nanosphere masks - Drude, Dennis; Brassat, Katharina; Brodehl, Christoph; Riedl, Thomas; Lindner, Jörg

Ag‐nanoparticles in PA-templates - Ezhova, A.; Lindner, Jörg; Muldarisnur, M.; Zentgraf, Thomas; Huber, K.

Influence of growth area reduction on cubic GaN heteroepitaxial layer growth on 3C-SiC(001) - Kemper, R.M.; Kovacs, A.; Riedl, Thomas; Meertens, D.; Tillmann, K.; As, D.; Lindner, Jörg

STEM-CL investigations on the influence of stacking faults on the optical emission of cubic GaN epilayers and cubic GaN/AlN multi-quantum wells - Kemper, R.M.; Veit, P.; Mietze, C.; Dempewolf, A.; Wecker, T.; Christen, J.; As, D.; Lindner, Jörg

Issues of Automated Software Composition in AI Planning - Mohr, Felix (Proceedings of the 29th International Conference on Automated Software Engineering (ASE))
Automated programming aims at automatically assembling a new software artifact from existing software modules. Although automated programming was revitalized through automated software composition in the last decade, the problem cannot be considered solved. Automated software composition is widely accepted as being a planning task, but the problem is that it has very special properties that other planning problems do not have and that are commonly overseen. These properties usually imply that the composition problem cannot be solved with standard planning tools. This paper gives a brief and intuitive description of the planning problem that most approaches are based on. It points out special properties of this problem and explains why it is not adequate to solve the problem with classical planning tools as done by most existing approaches.

Cubic GaN/AlN multi-quantum wells grown on pre-patterned 3C-SiC/Si (001) - Kemper, R. M.; Mietze, C.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report for the first time on the growth of cubic AlN/GaN multi‐quantum wells (MQWs) on pre‐patterned 3C‐SiC/Si (001) substrates. The sample structure consists of 10 periods of 2 nm c‐AlN barriers with a 4 nm c‐GaN layer in between, which were grown on 3C‐SiC post shaped structures by means of molecular beam epitaxy. Substrate patterning has been realized by electron beam lithography and a reactive ion etching process. The 3C‐SiC posts have a length of about 550 nm and a height of about 700 nm. (Scanning) transmission electron microscopy studies show that the morphology of the MQWs is clearly influenced by {111} stacking faults, modulating the local growth rate. Further, the growth at the edges of the surface pattern is investigated. The MQW layers cover the 90° edges by developing low‐index facets rather than by forming a conformal system of 90° angled layers.

Self-organized fabrication of periodic arrays of vertical, ultra-thin nanopillars on GaAs surfaces - Riedl, Thomas; Lindner, Jörg (physica status solidi (a))
This paper presents a low‐cost procedure that allows for self‐organized fabrication of periodically arranged, sub‐50 nm diameter, vertical‐sidewall GaAs nanopillars on GaAs surfaces based on nanosphere lithography, and reactive ion etching (RIE). Monodispersed polystyrene (PS) sphere double layers are deposited from a colloidal suspension on pre‐treated, hydrophilized GaAs substrates. Ni is thermally evaporated to act as a hard mask for subsequent RIE. Scanning electron microscopy reveals that the Ni nanoparticles left on the substrate after PS sphere removal have polygon‐shaped in‐plane cross‐sections corresponding to the shape of the double layer mask openings. RIE using SiCl4 at low pressure and high power density leads to the formation of vertical nanopillars with circular to oval cross‐sections, whose diameters are reduced by ∼1/3 compared to those of the Ni nanoparticles. These findings can be explained by plasma‐enhanced surface diffusion and sputtering processes during RIE. The obtained GaAs nanopillars have an average diameter of only ∼23 nm, exhibit an excellent verticality with a sidewall angle of 88.9 ± 0.4° and planar top faces, as visible in transmission electron microscopy images.

Thermal Modification of Nanoscale Mask Openings in Polystyrene Sphere Layers - Riedl, Thomas; Strake, Matthias; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
An experimental analysis of the morphology changes of hexagonally close packed polystyrene sphere monolayers induced by annealing in air is presented. The triangular interstices between each triple of spheres, which are frequently used as nanoscale mask openings in colloidal lithography, are observed to gradually shrink in size and change in shape upon annealing. Top view scanning electron microscopy images reveal that different stages are involved in the closure of monolayer interstices at annealing temperatures in the range between 110°C and 120°C. In the early stages shrinkage of the triangular interstices is dominated by material transport to and thus shortening of their corners, in the late stages interstice area reduction via displacement of the triangle edges becomes significant. At intermediate annealing times the rate of interstice area reduction displays a maximum before a stabilized state characterized by a rounded isosceles triangular shape forms.

Comparison of Theoretical Approaches Predicting the Coherent-Semicoherent Transition in Nanoscale Axial Heterostructures - Riedl, Thomas; Lindner, Jörg (Symposium YY – Elastic Strain Engineering for Unprecedented Materials Properties)
The formation of misfit dislocations is an important issue for the performance of heteroepitaxial micro- and optoelectronic devices. We analyze three approaches that quantify the stability of misfit dislocations in axial-heteroepitaxial nanowires with respect to applicability and predictions of critical nanowire dimensions. The “nanoheteroepitaxy” approach of Zubia and Hersee proves suitable for determination of strain partitioning in the presence of an elastic mismatch. Concerning the critical thickness and diameter however the descriptions of Ertekin et al. and Glas respectively yield more reliable results, owing to the consideration of the total coherent and dislocation related energies plus the residual strain energy. In contrast to the model of Ertekin et al., which refers to infinitely long nanowires, the other two mentioned approaches allow predictions of the critical thickness of mismatched deposits on the nanowire axial face.

Reliability of high-resolution electron backscatter diffraction determination of strain and rotation variations using phase-only and cross correlation - Riedl, Thomas; Wendrock, H. (Crystal Research and Technology)
This contribution analyzes the reliability of strain and rotation variation determination using cross‐ as well as phase‐only correlation of experimental wide‐angle electron backscatter diffraction (EBSD) patterns. For both rotation and three‐point bending the resulting displacement gradient tensor components are examined in terms of magnitude and statistical scatter as a function of various correlation procedure parameters and signal‐to‐noise ratio. It is shown that on the one hand the Fourier filter width has a major impact on the strain results. At higher noise level a smaller filter width has to be applied for obtaining maximum precision. On the other hand, the influence of the degree of overlap of the regions of interest positioned in the patterns is less important. For both rotation and bending experiments the cross‐correlation variant yields a smaller standard deviation with respect to phase‐only correlation, in particular for elevated noise level. The difference is attributed to the stronger propagation of noise effects in the course of phase‐only correlation function calculation and fitting. In the rotation experiment a standard deviation of ∼1.0 × 10^−4, averaged over the displacement gradient tensor components, and a rotational precision of ∼1.5 × 10^−4 rad have been achieved by using optimized evaluation settings.

Structure and surface chemistry analysis of ultra-thin reactive ion etched GaAs (111) nanopillars - Riedl, Thomas; Kovács, A.; Meertens, D.; Lindner, Jörg

RBS of gold-coated polystyrene nanospheres - Rüsing, M.; Merten, L.; Reinert, P.; Rogalla, D.; Becker, H.-W.; Lindner, Jörg

Integrating Software and Hardware Verification - Jakobs, Marie-Christine; Platzner, Marco; Wiersema, Tobias; Wehrheim, Heike (Proceedings of the 11th International Conference on Integrated Formal Methods (iFM))
Verification of hardware and software usually proceeds separately, software analysis relying on the correctness of processors executing instructions. This assumption is valid as long as the software runs on standard CPUs that have been extensively validated and are in wide use. However, for processors exploiting custom instruction set extensions to meet performance and energy constraints the validation might be less extensive, challenging the correctness assumption.In this paper we present an approach for integrating software analyses with hardware verification, specifically targeting custom instruction set extensions. We propose three different techniques for deriving the properties to be proven for the hardware implementation of a custom instruction in order to support software analyses. The techniques are designed to explore the trade-off between generality and efficiency and span from proving functional equivalence over checking the rules of a particular analysis domain to verifying actual pre and post conditions resulting from program analysis. We demonstrate and compare the three techniques on example programs with custom instructions, using stateof-the-art software and hardware verification techniques.

TEM investigations on the nanoheteroepitaxy of semiconductors - Lindner, Jörg

Microscopic studies of plasmonic nanostructures II - Lindner, Jörg

Nanostrukturierte Oberflächen, nicht nur zum Spass - Lindner, Jörg

Integrating Service Matchers into a Service Market Architecture - Platenius, Marie Christin; Becker, Steffen; Schäfer, Wilhelm (Proceedings of the 8th European Conference on Software Architecture (ECSA 2014))
Service markets provide software components in the formof services. In order to enable a service discovery that satisfies servicerequesters and providers best, markets need automatic service matching:approaches for comparing whether a provided service satisfies a servicerequest. Current markets, e.g., app markets, are limited to basic keywordbasedsearch although many better suitable matching approaches aredescribed in literature. However, necessary architectural decisions forthe integration of matchers have a huge impact on quality propertieslike performance or security.Architectural decisions wrt. servicematchers have rarely been discussed,yet, and systematic approaches for their integration into service marketsare missing. In this paper, we present a systematic integration approachincluding the definition of requirements and a discussion on architecturaltactics. As a benefit, the decision-making process of integrating servicematchers is supported and the overall market success can be improved.

RSDL workbench results for OAEI 2014 - Schwichtenberg, Simon; Gerth, Christian; Engels, Gregor (Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference (ISWC 2014), Riva del Garda, Trentino, Italy, October 20, 2014.)

Incorporating Reputation Information into Decision-Making Processes in Markets of Composed Services - Jungmann, Alexander; Brangewitz, Sonja; Petrlic, Ronald; Platenius, Marie Christin (International Journal On Advances in Intelligent Systems (IntSys))
One goal of service-oriented computing is to realize future markets of composed services. In such markets, service providers offer services that can be ﬂexibly combined with each other. However, although crucial for decision-making, market participants are usually not able to individually estimate the quality of traded services in advance. To overcome this problem, we present a conceptual design for a reputation system that collects and processes user feedback on transactions, and provides this information as a signal for quality to participants in the market. Based on our proposed concept, we describe the incorporation of reputation information into distinct decision-making processes that are crucial in such service markets. In this context, we present a fuzzy service matching approach that takes reputation information into account. Furthermore, we introduce an adaptive service composition approach, and investigate the impact of exchanging immediate user feedback by reputation information. Last but not least, we describe the importance of reputation information for economic decisions of different market participants. The overall output of this paper is a comprehensive view on managing and exploiting reputation information in markets of composed services using the example of On-The-Fly Computing.

Improving Service Specifications for the Service Matching on a Service Market - Taherinajafabadi, Vahide

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias; Scheideler, Christian; Graffi, Kalman (Proceedings of the 14th IEEE International Conference on Peer-to-Peer Computing (P2P))
In this paper we present and analyze HSkip+, a self-stabilizing overlay network for nodes with arbitrary heterogeneous bandwidths. HSkip+ has the same topology as the Skip+ graph proposed by Jacob et al. [PODC 2009] but its self-stabilization mechanism significantly outperforms the self-stabilization mechanism proposed for Skip+. Also, the nodes are now ordered according to their bandwidths and not according to their identifiers. Various other solutions have already been proposed for overlay networks with heterogeneous bandwidths, but they are not self-stabilizing. In addition to HSkip+ being self-stabilizing, its performance is on par with the best previous bounds on the time and work for joining or leaving a network of peers of logarithmic diameter and degree and arbitrary bandwidths. Also, the dilation and congestion for routing messages is on par with the best previous bounds for such networks, so that HSkip+ combines the advantages of both worlds. Our theoretical investigations are backed by simulations demonstrating that HSkip+ is indeed performing much better than Skip+ and working correctly under high churn rates.

Horizontale Fusionen: Theorie und Praxis am Beispiel zweier Entscheidungen des Bundeskartellamtes - Eusterholz, Fabian

Hiding software components using functional encryption - Jochheim, Janek

Handling Incomplete Service Specifications using Fuzzy Matching - Vijapurwala, Shafi

Group Signature Schemes with Strong Exculpability - Bemmann, Pascal

Grammar-based model transformations - Besova, Galina; Steenke, Dominik; Wehrheim, Heike (Proceedings 3rd Workshop on Model Driven Approaches in System Development (MDASD))
Model transformation is a key concept in modeldrivensoftware engineering. The definition of model transformationsis usually based on meta-models describing the abstractsyntax of languages. While meta-models are thereby able to abstractfrom superfluous details of concrete syntax, they often loosestructural information inherent in languages, like information onmodel elements always occurring together in particular shapes.As a consequence, model transformations cannot naturally re-uselanguage structures, thus leading to unnecessary complexity intheir development as well as analysis.In this paper, we propose a new approach to model transformationdevelopment which allows to simplify and improve thequality of the developed transformations via the exploitation ofthe languages’ structures. The approach is based on context-freegrammars and transformations defined by pairing productions ofsource and target grammars. We show that such transformationsexhibit three important characteristics: they are sound, completeand deterministic.

Generierung von Eigenschaftsprüfern in einem Hardware/Software-Co-Verifikationsverfahren - Pauck, Felix

Gender and ethnic discrimination in hiring : evidence from field experiments in the German labor market - Kolle, Andre
The present thesis investigates the prevalence of and the reasons for hiring discrimination against women and ethnic Turks in the German labor market. Subsequent to a discussion of how to reveal discrimination, the literature on wage and employment differences inside and outside the German labor market is reviewed. Afterwards, different (economic) theories explaining inequalities in labor markets are presented. In the empirical analyses a field experiment - the so called correspondence testing - is conducted where matched pairs of (fictitious) male and female as well as German-named and Turkish-named applicants respond to, respectively, 656 and 608 (real) apprenticeship offers in predominantly male-dominated jobs. Descriptive results and econometric analyses using probit regressions on various model specifications indicate that the female applicant has a 19 percent lower callback probability compared to her male counterpart. However, differential treatment is both job- and firm-type driven. While callback rates are not statistically different from zero in female-dominated and “gender-neutral” occupations, they prevail in jobs where men are overrepresented. Furthermore, discrimination is restricted to late recruiters, i.e., companies that advertise their vacancies right before the apprenticeship is supposed to start. Similar conclusions can be drawn from the study investigating ethnic discrimination. The 32 percent lower callback probability of the Turkish-named applicant decreases if early rather than late recruiters are addressed. Apart from that, comparing response and callback rates to the candidates using different experimental designs, i.e., sending out single versus pairs of applications, yields no statistically significant differences demonstrating the unbiasedness of the correspondence approach.

Fuzzy Matching of Service Price Specifications - Merschjohann, Sven

Fujisaki-Okamoto Transformation - Lippert, Jan

Formal Semantics of Probabilistic SMT Solving in Verification of Service Compositions - Sanati, Maryam

Finding Optimal Self-Adaption Rules by Design-Space Exploration - Jojiju, Suman

Fast and Flexible Automatic Composition of Semantic Web Services - Finkensiep, Christoph

Evaluation of Color Spaces for Robust Image Segmentation - Jungmann, Alexander; Jatzkowski, Jan; Kleinjohann, Bernd (Proceedings of the 9th International Conference on Computer Vision Theory and Applications (VISAPP))
In this paper, we evaluate the robustness of our color-based segmentation approach in combination with different color spaces, namely RGB, L*a*b*, HSV, and log-chromaticity (LCCS). For this purpose, we describe our deterministic segmentation algorithm including its gradually transformation of pixel-precise image data into a less error-prone and therefore more robust statistical representation in terms of moments. To investigate the robustness of a specific segmentation setting, we introduce our evaluation framework that directly works on the statistical representation. It is based on two different types of robustness measures, namely relative and absolute robustness. While relative robustness measures stability of segmentation results over time, absolute robustness measures stability regarding varying illumination by comparing results with ground truth data. The significance of these robustness measures is shown by evaluating our segmentation approach with different color spaces. For the evaluation process, an artificial scene was chosen as representative for application scenarios based on artificial landmarks.

Evaluation of a Hybrid Packet-/Circuit-Switched Data Center Network - Dornseifer, Veit

Evaluating the Influence of Different Abstraction Levels of Software Design on Performance prediction - Bulk, Benjamin

Estimating Functional Reusability of Services - Mohr, Felix (Proceedings of the 12th International Conference on Service Oriented Computing (ICSOC))
Services are self-contained software components that can be used platform independent and that aim at maximizing software reuse. A basic concern in service oriented architectures is to measure the reusability of services. One of the most important qualities is the functional reusability, which indicates how relevant the task is that a service solves. Current metrics for functional reusability of software, however, either require source code analysis or have very little explanatory power. This paper gives a formally described vision statement for the estimation of functional reusability of services and sketches an exemplary reusability metric that is based on the service descriptions.

Entwicklung eines mathematischen Modells zur Optimierung der Struktur eines Trinkwasserbehälters - Herbort, Maik

Entwicklung eines Konzepts zur Kodierung eines objektorientierten Typsystems in SMT - Krakau, Andreas

Energy-efficient Scheduling Algorithms - Kling, Peter
In meiner Dissertation beschäftige ich mich mit dem Entwurf und der Analyse energieeffizienter Schedulingalgorithmen, insbesondere für sogenannte Speed-Scaling Modelle. Diese stellen das theoretische Pendant von Techniken wie AMDs PowerNOW! und Intels SpeedStep dar, welche es erlauben die Geschwindigkeit von Prozessoren zur Laufzeit an die derzeitigen Bedingungen anzupassen. Theoretische Untersuchungen solcher Modelle sind auf eine Arbeit von Yao, Demers und Shenker (FOCS'95) zurückzuführen. Hier kombinieren die Autoren klassisches Deadline-Scheduling mit einem Prozessor der Speed-Scaling beherrscht. Es gilt Jobs verschiedener Größe fristgerecht abzuarbeiten und die dabei verwendete Energie zu minimieren. Der Energieverbrauch des Prozessors wird durch eine konvexe Funktion $\POW\colon\R_{≥0}→\R_{≥0}$ modelliert, welche die Geschwindigkeit auf den Energieverbrauch abbildet.Meine Dissertation betrachtet verschiedene Varianten des ursprünglichen Speed-Scaling Modells. Forschungsrelevante Ergebnisse sind in den Kapiteln 3 bis 6 zu finden und erstrecken sich über die im Folgenden beschriebenen Aspekte:- Kapitel 3 und 4 betrachten verschiedene Price-Collecting Varianten des Originalproblems. Hier dürfen einzelne Deadlines verfehlt werden, sofern eine jobabhängige Strafe gezahlt wird. Ich entwerfe insbesondere Online-Algorithmen mit einer beweisbar guten Competitiveness. Dabei liefern meine Ergebnisse substantielle Verbesserungen bestehender Arbeiten und erweitern diese unter Anderem auf Szenarien mit mehreren Prozessoren.- In Kapitel 5 wird statt des klassischen Deadline-Schedulings eine Linearkombination der durchschnittlichen Antwortzeit und des Energieverbrauchs betrachtet. Die Frage, ob dieses Problem NP-schwer ist, stellt eine der zentralen Forschungsfragen in diesem Gebiet dar. Für eine relaxierte Form dieser Frage entwerfe ich einen effizienter Algorithmus und beweise seine Optimalität.- Das letzte Kapitel betrachtet ein Modell, welches – auf den ersten Blick – nicht direkt zur Speed-Scaling Literatur zählt. Hier geht es stattdessen um ein allgemeines Resource-Constrained Scheduling, in dem sich die Prozessoren zusammen eine gemeinsame, beliebig aufteilbare Ressource teilen. Ich untersuche die Komplexität des Problems und entwerfe verschiedene Approximationsalgorithmen.

Light Scattering By Random Irregular Particles With Different Morphology - Grynko, Yevgen; Zubko, Evgenij
We simulate numerically light scattering by random irregular particles of two classes of shape: Gaussian random field particles and agglomerated debri particles. Comparison of the angular dependencies of the scattering matrix elements for the case of non-absorbing material shows qualitative similarity of optical properties of both types despite different morphology of scatterers. Absorbing particles result in the difference in linear polarization. However, a strong similarty remains for the intensity curves.

Energy-Efficient Queuing with Delayed Deactivation - Bredenbals, Nico

Embedding FPGA Overlays into Configurable Systems-on-Chip: ReconOS meets ZUMA - Wiersema, Tobias; Bockhorn, Arne; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Virtual FPGAs are overlay architectures realized on top of physical FPGAs. They are proposed to enhance or abstract away from the physical FPGA for experimenting with novel architectures and design tool flows. In this paper, we present an embedding of a ZUMA-based virtual FPGA fabric into a complete configurable system-on-chip. Such an embedding is required to fully harness the potential of virtual FPGAs, in particular to give the virtual circuits access to main memory and operating system services, and to enable a concurrent operation of virtualized and non-virtualized circuitry. We discuss our extension to ZUMA and its embedding into the ReconOS operating system for hardware/software systems. Furthermore, we present an open source tool flow to synthesize configurations for the virtual FPGA.

Radio Frequency Electromechanical Control over a Surface Plasmon Polariton Coupler - Ruppert, Claudia; Förster, Frederike; Zrenner, Artur; Kinzel, Jörg B.; Wixforth, Achim; Krenner, Hubert J.; Betz, Markus (ACS Photonics)
We explore the impact of ∼500 MHz surface acoustic waves traveling across a commensurable plasmonic grating coupler. A stroboscopic technique involving surface acoustic waves synchronized to a modelocked optical source allows to time-resolve the dynamical impact of the electromechanically induced perturbation. The surface acoustic wave periodically enhances or decreases the surface ripple of the static grating. Most remarkably, the dynamic surface deformation deliberately modulates the coupler’s efficiency by ±2% during the ∼2 ns acoustic cycle.
Keywords: nanomechanics; plasmonics; surface acoustic waves; surface plasmon polaritons

Ein selbst-stabilisierender Algorithmus für das Finite Sleep Problem in Skip+ Graphen - Luo, Linghui

Efficient Computation of Optimal Energy and Fractional Weighted Flow Trade-off Schedules - Antoniadis, Antonios; Barcelo, Neal; Consuegra, Mario; Kling, Peer; Nugent, Michael; Pruhs, Kirk; Scquizzato, Michele (Proceedings of the 31st Symposium on Theoretical Aspects of Computer Science (STACS))
We give a polynomial time algorithm to compute an optimal energy and fractional weighted flow trade-off schedule for a speed-scalable processor with discrete speeds.Our algorithm uses a geometric approach that is based on structural properties obtained from a primal-dual formulation of the problem.

Easy-to-use on-the-fly binary program acceleration on many-cores - Damschen, Marvin

Die ökonomischen Auswirkungen der Kronzeugenregelung am Beispiel des Kaffeerösterkartells - Wemhöner, Vanessa

Designing an Anonymous and Secure Reputation System Using a Group Signature Variant - Kokoschka, Andreas

Decision Making under Asymmetric Information in Markets for Experience Goods: Empirical Evidence of Signaling Effects on Consumer Perceptions - Kaimann, Daniel

Vermögensteuer als Beitrag der Wohlhabenden für mehr Gleichheit - eine wirtschaftswissenschaftliche Betrachtung eines Steuerreformvorschlags - Sureth-Sloane, Caren (Wirtschaftspädagogische Handlungsfelder)

Effizienzmessung industrieller Dienstleistungen mittels Data Envelopment Analysis (ServDEA) - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Bröker, Ole; Alexander Brüne, Philipp; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans; Reichle, Florian; Wilken, Robert (Produktivität von Dienstleistungen)

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities - Kortebusch, Pia